Pengaruh Perendaman Asam Sulfat (H2SO4) Terhadap Viabilitas Benih Delima (Punica granatum L.) - Ilham Indra Satya; Haryati Haryati; Toga Simanungkalit (Jurnal Agroekoteknologi, 2015)
Pomegranate seed requires dormancy breaking treatment to encourage germination. One of dormancy breaking treatments that can be done is soaking on sulphuric acid (H2SO4). This study aimed to determine the effect of concentration and duration of soaking sulphuric acid (H2SO4) on the viability of pomegranate seeds. This research was conducted at the Laboratory of Seed Technology Faculty of Agriculture, University of Sumatra Utara, Medan with a height of ± 25 meters above sea level, in April 2015, using a completely randomized design with 10 degree factor dormancy breaking treatments that seed soaking treatment with H2SO4 (25%, 50%, 75%) with duration of soaking (10 minutes, 15 minutes, and 20 minutes). Parameters measured were tetrazolium test (%), germination rate (day), normal seedling (%), abnormal seedling (%), seed that has not grown (%), vigor index, fresh weight seedling (g), dry weight seedling (g). The results showed that seed soaking treatment with 75% H2SO4 for 10 minutes increased the percentage of germination rate (day), normal seedling (%),vigor index, fresh weight seedling (g), dry weight seedling (g), but not to tetrazolium test (%).Keywords: pomegranate seeds, viability, dormancy, sulphuric acid